Financial and Economic Safety: Formal Statement of the Task of Capital Flows Management - Likhtenshtein, V.Ye.; Los, V.P.; Ross, G.V.; Tyshuk, E.D. (International Journal of Engineering and Technology, 2018)
The problem of global financial and economic security is considered. A substantive and formal formulation of the problem of capital flow modeling is formulated, based on two groups of theorems on economic management mechanisms: the planned mechanism and the market mechanism. The main characteristics of capital flow assessment are revealed.This is an analysis of the situation in which it can be interpreted. The structure of the flow of water and the market mechanism were determined and proposed.